Early olfactory dysfunction in experimental autoimmune encephalomyelitis reflects transient brain barrier breach and initiation of neuroinflammation in the olfactory bulb - Stekic, Andjela; Dragic, Milorad; Stevanovic, Ivana; Zaric Kontic, Marina; Adzic Bukvic, Marija; Dacic, Sanja; Ninkovic, Milica; Nedeljkovic, Nadezda (Frontiers in Cellular Neuroscience, 2025)
Olfactory dysfunction is increasingly recognized as an early, non-motor manifestation of multiple sclerosis (MS), but the mechanisms underlying its occurrence remain unclear. Using the rat model of experimental autoimmune encephalomyelitis (EAE), we investigated the temporal relationship between olfactory impairment, neuroinflammation, barrier integrity, and adenosine signaling in the olfactory bulb (OB) in the early stage of EAE. The study showed that more than two-thirds of EAE animals exhibited significant deficits in the buried food test as early as 3 days post-immunization (dpi), which preceded the first motor symptoms by several days. Open field test confirmed that these olfactory deficits were not due to impaired locomotion. Transient breach to the OB tissue barrier was demonstrated at 3–5 dpi by increased FITC-dextran penetration and peripheral monocyte/macrophage infiltration into the lateral aspect of the OB. The breach coincided with activation of microglia in the outer nerve layer on the lateral aspect of the OB. Oxidative stress, including elevated malondialdehyde, nitric oxide, and superoxide ion levels along with a depleted antioxidant defense system, indicated a redox imbalance, while a transient increase in neurofilament light chain serum levels at 3 dpi indicated acute neuroaxonal injury and barrier disruption at early stage EAE. At the molecular level, the simultaneous upregulation of CD73 and adenosine A1/A2A receptors along the pial surface and in the olfactory nerve layer suggested enhanced adenosine signaling in early barrier modulation. Spatial mapping of FITC-dextran penetration, peripheral infiltrates, and microglia activation indicated access of immune cells from the subarachnoid space into the OB parenchyma. Overall, these results demonstrate that the OB is a permissive entry zone for autoreactive immune cells in the OB in early stages of EAE, highlighting olfactory and behavioral testing as promising tools for early detection and monitoring of MS.